2020
DOI: 10.1111/1742-6723.13510
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic haemostatic assays in aeromedical transport

Abstract: Objective: To assess the feasibility of using rotational thromboelastometry (ROTEM ®)-sigma and thromboelastography (TEG ®)-6s viscoelastic pointof-care assays during rotary wing aeromedical transport, and to determine the reliability of the results obtained. Methods: A single centre, prospective, observational, non-interventional feasibility study performed at Gold Coast University Hospital intensive care unit, and in a LifeFlight Retrieval Medicine operated Leonardo AW139 helicopter. Blood was collected from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…However, studies in the prehospital urban population are in process, and we expect those insights to be similarly adapted in the far-forward environment as they have been in the past. While individual circumstances may still present challenges that will require further study to mitigate, we broadly envision VHA utilization in a stepwise manner in both far-forward and the austere environments similar to that initially proposed by Bates et al (Figures 2 and 3) [102].…”
Section: Time To Actionable Informationmentioning
confidence: 91%
See 3 more Smart Citations
“…However, studies in the prehospital urban population are in process, and we expect those insights to be similarly adapted in the far-forward environment as they have been in the past. While individual circumstances may still present challenges that will require further study to mitigate, we broadly envision VHA utilization in a stepwise manner in both far-forward and the austere environments similar to that initially proposed by Bates et al (Figures 2 and 3) [102].…”
Section: Time To Actionable Informationmentioning
confidence: 91%
“…Given that transport from the far-forward and austere environment can take considerable time, en route [or prehospital] care is arguably the next best setting to develop protocols for the use of VHAs. Prehospital VHAs in the far-forward combat and civilian austere environment may be useful to guide (1) initial resuscitation before transport, (2) resuscitation en route by air or ground transport, and (3) additional resuscitation on arrival to the combat support or rural hospital [102]. Expansion of VHA use in the prehospital setting as an adjunct to the administration of WB is necessarily limited by the reliability of TEG ® /ROTEM ® under commonly encountered environmental insults.…”
Section: Transportmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, initial experiments yielded promising results when the TEG6s was exposed to shaking and sudden strikes during measurements. Several experimental and one prehospital inflight study revealed conflicting results [19][20][21][22]. In order to evaluate in detail the factors that potentially influence the analytical quality of TEG6s during in-flight missions, we compared test results during helicopter operations with results that were obtained on the ground.…”
Section: Introductionmentioning
confidence: 99%